Hydrothermal carbonization of microalgae for phosphorus recycling from wastewater to crop-soil systems as slow-release fertilizers. (10th February 2021) - Chu, Qingnan; Lyu, Tao; Xue, Lihong; Yang, Linzhang; Feng, Yanfang; Sha, Zhimin; Yue, Bin; Mortimer, Robert J.G.; Cooper, Mick; Pan, Gang
Abstract: Due to the finite stocks of phosphate rock and low phosphorus (P) use efficiency (PUE) of traditional mineral P fertilizers, more sustainable alternatives are desirable. One possibility is to culture microalgae in wastewater to recover the P and then convert the microalgae biomass into slow-release fertilizers through hydrothermal carbonization (HTC). Therefore, this study aimed to recycle P from wastewater to agricultural field using microalgae and HTC technology. Chlorella vulgaris (CV) and Microcystis sp. (MS) were cultured in poultry farm wastewater with an initial concentration of 41.3 mg P kg −1 . MS removed 88.4% P from the wastewater, which was superior to CV. CV- and MS-derived hydrochars were produced at 200 or 260 °C, in solutions using deionized water or 1 wt % citric acid. The MS-derived hydrochar using 1 wt % citric acid solution at 260 °C (MSHCA260) recovered the highest amount of P (91.5%) after HTC. The charring promoted the transformation of soluble and exchangeable P into moderately available P (Fe/Al-bound P), and using citric acid solution as feedwater increased the P recovery rate and formation of Fe/Al-bound P. With the abundant moderately available P pool, hydrochar amendment released P more slowly and enhanced the soil P availability more persistently than chemical fertilizer did, which helped to improve PUE. In a wheat-cultivation pot experiment, MSHCA260 treatment improved wheat PUE by 34.4% and yield by 21.6% more than chemical fertilizer did. These results provide a novel sustainable strategy for recycling P from wastewater to crop-soil systems, substituting the mineral P fertilizer, and improving plant PUE. Graphical abstract: Image 1 Highlights: Chlorella vulgaris and Microcystis sp. (MS) removed 78.7% and 88.4% phosphorous (P). 91.5% P was recovered from MS to MS-derived hydrochar produced at 260 °C (MSHCA260). Microalgal hydrochars slowly released P and improved soil P availability. MSHCA260 increased P use efficiency and wheat yield compared to chemical fertilizer. Microalgae and hydrochar technology recycled P from wastewater to crop food.